Therapeutic effects and mechanisms of N-(9,10-anthraquinone-2-ylcarbonyl) xanthine oxidase inhibitors on hyperuricemia - Gao, Tianshu; Xu, Jin; Xiao, Yuxiao; Li, Jiaqi; Hu, Weifeng; Su, Xiaoyu; Shen, Xudong; Yu, Wan; Chen, Zhen; Huang, Baosheng; Li, Honglei; Wang, Xing (Frontiers in Pharmacology, 2022)
Objective: To observe the antioxidative effects of N-(9,10-anthraquinone-2-ylcarbonyl) xanthine oxidase inhibitors (NAY) in vitro and in vivo models of hyperuricemia and explore the mechanism. Methods: A classical experimental method of acute toxicity and a chronic toxicity test were used to compare the toxic effects of different doses of anthraquinone xanthine oxidase inhibitor (NAY) in mice. Hyperuricemia mouse model was established by gavage of potassium oxazinate in vivo. After treatment with different doses of NAY and allopurinol, observe levels of uric acid, creatinine and urea nitrogen in urine and serum respectively and detect the activities of xanthine oxidase in liver. Hyperuricemia cell model was induced by adenosine and xanthine oxidase in vitro. Cells were given different doses of NAY and allopurinol. Then the culture supernatant uric acid level of the medium was measured. The next step was to detect the xanthine oxidase activity in liver and AML12 cells, and the levels of TNF-α, IL-6, and other inflammatory factors in kidney and serum of mice. Western blot was used to detect xanthine oxidase protein expression in mouse liver tissue and AML12 cells, ASC, Caspase-1, NLRP3, GLUT9, OAT1 and OAT3 protein expression in mouse kidney tissue and HK-2 cells. Hematoxylin-eosin staining was used to stain the liver and kidney tissues of mice, and observe the tissue lesions. Results: NAY had little effect on blood routine and biochemical indexes of mice, but significantly reduced serum uric acid level. NAY significantly reduced the level of uric acid in hyperuricemia mice and cells by inhibiting xanthine oxidase activity, and reduced the levels of TNF-α and other inflammatory factors in serum and kidney of mice. NAY can inhibit inflammation by inhibiting NLRP3 pathway. NAY can down-regulate GLUT9 protein expression and up-regulate OAT1 and OAT3 protein expression to reduce uric acid level by promoting uric acid excretion and inhibiting uric acid reabsorption. Conclusion: These findings suggested that NAY produced dual hypouricemic actions. On the one hand, it can inhibit the formation of uric acid by inhibiting xanthine oxidase inhibitors activity, on the other hand, it can promote the excretion of uric acid by regulating the uric acid transporter.